Evaluasi Tingkat Keandalan Sistem Distribusi 20 kV Menggunakan Indeks SAIDI SAIFI - Nurmiati Pasra; Samsurizal Samsurizal; Muh Fajri (Sekolah Tinggi Teknik - PLN, 2022)
Reliability describes the proportion of service level when power is delivered from the system to the customer. PT. PLN (Persero) UP3 Biak still experiences frequent power outages due to fallen trees, animal activities such as snakes, and disturbances due to blackouts due to bad weather, which affects the reliability value. By using SAIDI and SAIFI to determine the level of reliability at PT. PLN (Persero) UP3 Biak, then based on the standards that have been determined by the Main Unit for the Papua and West Papua Regions with a SAIDI value of 10.11 hours/customer/year and SAIFI = 9.72 times/customer/year. For this reason, periodic maintenance is carried out such as tree removal, installation of fibers, installation of insulators and repair of SUTM and SUTR constructions. After the maintenance, the results showed that there was a change in the value of SAIDI and SAIFI, namely ULP Biak City, the value of SAIDI = 5.9 hours/customer and SAIFI = 4.98 times/customer with a percentage decrease of 87.6% and 88.8%, respectively. ULP Yumdori value SAIDI = 11.48 hours/customer and SAIFI = 5.97 times/customer with a percentage decrease of 90.1% and 94.3%, respectively. ULP Serui value SAIDI = 6.48 hours/customer and SAIFI = 3.79 times/customer with a percentage decrease of 83.4% and 86.9%. ULP Waropen value SAIDI = 0.77 hours/customer and SAIFI = 0.95 times/customer with a percentage decrease of 92.2% and 86%, respectively.